PERJANJIAN WARALABA DALAM PERSPEKTIF BISNIS SYARI`AH - Dr. Abdullah Taufik, M.HI. (Fakultas Syariah IAIN Kediri, 2018)
Intellectual property rights as the crystallization of someone's hard work in discoveries, literary and artistic works, the images of extraordinary value as a result of the development of science and technology. The franchise system contains an abstract wealth that has high economic value such as, images or good name (good will) that is required in the business world as an effort to seize the market share that plays a very big role. In relation to the amount of rewards received by the Franchise or as the owner of intellectual property rights, to be reviewed in the next Sharia’s perspective.